Water-rock-ore Interaction (on Example: Major Bakchar Iron-ore Deposit – Western Siberia, Russia); Procedia Earth and Planetary Science; Vol. 17 : 15th Water-Rock Interaction International Symposium, WRI-15 - Lepokurova О. Е. Olesya Evgenyevna (2017, 2017)
Title screen